Acute gastrointestinal bleeding from a chronic cause: a teaching case report - Michaël R. Laurent; Lode Van Overbeke (WikiJournal of Medicine, 2017)
Gastrointestinal bleeding (GI bleed) is a common and potentially life-threatening reason for emergency room and intensive care unit admission. This article reports the case of an 83-year-old man with acute GI bleeding from an unusual cause. The clinical information is presented in a step-by-step and question-answer format for learning purposes. This paper is particularly aimed at an internal medicine readership.